Social Support for the War-Wounded of Military Physically Disabled - صالح, ليندا (Latakia University Journal -Medical Sciences Series, 2020)
Social support with its various sources, such as family, friends, and community institutions, is of great importance for the physically disabled, and given the resulting casualties of the Syrian Arab Army to preserve the country from injuries that resulted in physical disabilities among the heroic soldiers, the present descriptive study aimed to assess the social support provided to the war-wounded military physically disable, in the Department of Physical Therapy at Tishreen University Hospital in Lattakia, where the basic study sample included 50 wounded from the Syrian Arab Army who have a physical disability caused by war injuries. They were chosen using the available sample method. Data were collected using a questionnaire prepared for this purpose. This study showed that the level of social support provided by the family was large, and it was moderate by friends, while it was a little by the community institutions, and the level of general social support was moderate. It recommended the need to give the physically disabled the confidence and acceptance by friends and society and give them a major role in taking leadership and community roles, and increase interest by society institutions in the physically disabled and work to provide support and assistance in all its forms and dimensions, and design educational and training programs by specialists to targeting family and friends of physically disabled, to show them the importance of social support in changing the lives of these physically disabled a better life, and to conducting more researches on all aspects of support that can be provided to the military physically disabled in order to improve the quality of their lives.